Assessing the Resilience of Primary Health Care Services: Evidence from Public Health Centers in Depok City - Nurazizah, Venni (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aims to quantitatively assess the resilience level of primary health care services at Public Health Centers (Puskesmas) in an urban setting by measuring multiple resilience dimensions under routine service conditions in Depok City, Indonesia. Methodology: This quantitative descriptive cross-sectional study used a structured questionnaire based on the WHO Primary Health Care Measurement Framework and the Oktari–Kurniawan resilience model. Data were collected via Google Forms from 100 purposively selected Puskesmas staff and analyzed using descriptive statistics with univariate analysis. Main Findings: The findings show that primary health care services demonstrated high resilience across all assessed dimensions. Good resilience was reported for physical conditions (83%), institutional roles (88%), staff capacity (83%), external relationships (84%), and environmental exposure (81%), indicating strong organizational readiness and service continuity at the primary care level. Novelty/Originality of this study: This study provides novel quantitative evidence on primary health care resilience during routine, post-crisis operational conditions rather than emergency phases. It integrates five resilience dimensions within a single empirical framework at the Puskesmas level, contributing localized urban evidence to strengthen primary health care resilience assessment and policy development.